Overexpression of GmUBC9 Gene Enhances Plant Drought Resistance and Affects Flowering Time via Histone H2B Monoubiquitination - Chen, Kai; Tang, Wen-Si; Zhou, Yong-Bin; Xu, Zhao-Shi; Chen, Jun; Ma, You-Zhi; Chen, Ming; Li, Hai-Yan (Frontiers in Plant Science, 2020)
Post-translational modifications of proteins by ubiquitylation can regulate processes including protein degradation and localization, protein-protein interactions, and transcriptional activation. During ubiquitylation, substrate specificity is primarily determined by an E2 ubiquitin-conjugating enzyme (UBC) and an E3 ubiquitin ligase. Multiubiquitination modifies target proteins for final degradation by the 26S proteasome, and monoubiquitination regulates the localization and activation of the target proteins. At present, research on the monoubiquitination, especially histone monoubiquitination, has mostly focused on model plants with relatively few on crop species. In this study, 91 UBC-like genes were identified in soybean. The chromosomal localization, phylogenetic relationships, gene structure, and putative cis-acting elements were analyzed. Furthermore, the tissue-specific expression patterns of UBC Class I genes under drought stress were also investigated. Among Class I genes, GmUBC9 was significantly induced by water deficit stress and selected for further analysis. GmUBC9 localized to the nucleus and endoplasmic reticulum. The overexpression of GmUBC9 in Arabidopsis improved drought tolerance at different developmental stages, while overexpression in soybean hairy roots enhanced drought tolerance, increased proline content, and reduced MDA content in soybean seedlings compared to wild type plants. HISTONE MONOUBIQUITINATION 2 (HUB2), an E3-like protein involved in histone H2B ubiquitylation (H2Bub1), was found to interact with GmUBC9 through Y2H analysis and BiFC assays in Arabidopsis and soybean. Under drought conditions, the level of H2Bub1 increased and transcription of drought response genes was activated in GmUBC9 transgenic Arabidopsis and soybean. In addition, GmUBC9 transgenic Arabidopsis and soybean showed a late-flowering phenotype and had increased expression levels of the flowering related genes FLC and MAF4. These results indicate that GmUBC9 plays important roles in drought stress response and regulation of flowering time in soybean.